Understanding fully online teaching in vocational education - Deniese Cox; Sarah Prestridge (The Asia-Pacific Society for Computers in Education (APSCE), 2020)
Abstract Literature has previously reported that student-centred practices are the mark of good pedagogy in online education. In contrast, the competency-based nature of vocational education in Australia has been understood to encourage teacher-centred pedagogy. The likely tensions between these two teaching contexts are not yet understood, and little is yet known about the pedagogy of fully online vocational education teachers. To begin understanding pedagogy in this context, a wide-ranging digital survey was implemented. Findings revealed that online vocation education teachers conceived good online pedagogy as student-centred, yet student-student learning opportunities were rated lower than teacher-student practices. Notably, enacted practice was consistently more teacher-centred than teachers' ideal, and factors within the teaching context were perceived by teachers as a limitation. They reported their workload to be dominated by marking and administration ahead of student-centred practices such as building rapport. This work is of interest to researchers and institutions navigating the continued expansion of online education and the ongoing demand for effective student-centred practice.